GAMBARAN POLA MAKAN PADA PENDERITA HIPERTENSI DI DESA PAYA BAROO KECAMATAN TEUNOM, KABUPATEN ACEH JAYA - Kala, Pasyamei Rembune; Listina, Meri (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
Hypertension is one of the major health problems in Indonesia, including in Paya Baroo Village, Teunom District, Aceh Jaya Regency. An unhealthy diet can be a major risk factor for hypertension. This study aims to provide an overview of dietary patterns in people with hypertension in Paya Baroo Village. This study used a qualitative descriptive approach. Data were collected through structured interviews using a customized questionnaire. Respondents were hypertensive patients in Paya Baroo Village who had been diagnosed by local health workers. Data analysis was conducted by detailing dietary patterns based on food types, frequency of consumption, and dish patterns. The results showed that most hypertensive patients in Paya Baroo Village had a diet that tended to be high in salt, fat and cholesterol. Fruit and vegetable consumption still did not reach the recommended recommendations. There is a tendency to consume fast food and canned food which can increase the risk of hypertension. Some respondents also have a habit of consuming traditional high-salt foods such as salted fish and fatty side dishes. This study highlights the need for interventions to improve community understanding of healthy eating patterns and their impact on health, especially for people with hypertension living in Paya Baroo Village. Health education and promotion of healthy lifestyles need to be improved to reduce risk factors associated with unhealthy diets in this population. Preventive measures such as health campaigns and counseling can be effective strategies in addressing this issue at the local community level.